A study on the services provided by operation counter ASNB Melaka branches to their customer / Nor Hazliza Zakaria - Zakaria, Nor Hazliza (Faculty of Business and Management, 2009)
Service quality has recently become a concern for Malaysian government agencies since the entrepreneurial spirit and the development of information technology pervades in the new economy. This study examines the level of service operation counter with special reference to ASNB Melaka using SERVQUAL dimensions as the instrument. The analysis has proven the reliability and universality of Service Quality or SERVQUAL dimensions upon determining the level of service operation counter within the statutory body such ASNB Melaka. Using the 19-item SERVQUAL survey instrument, the findings highlight five key determinants of customer experienced that comprises of Tangibles, Responsiveness, Reliability, Assurance and Empathy. In determining the level of service quality, a Likert-type survey was developed and tested. Gather customer satisfaction within the ASNB Melaka is difficult and tiring task, however, it is necessary for ASNB Melaka to emphasis on the development of human elements and technical equipment to ensure the increase in the number of customers to generate higher revenue in future. Focusing on the five SERVQUAL dimensions shall undoubtedly lead the customer to enhancing loyalty retention and ensuring business longevity. Therefore, in this research, researcher try to observe concept of service quality, service operation counter, service quality dimension to examine whether all these dimensions perform effectively towards the operation counter at ASNB Melaka.